Engineering the composition and fate of wild populations with Medea and ClvR: uses and development of ClvR - Hay, Bruce A. (Henry Stewart Talks, 2023)
Gene drive, The use of inteins with ClvR, Cycles of success and failure, Control of transgene fate post-release, 2-locus CLvR mechanism of action